Pengolahan Air Limbah Pasar Al Mahira Lamdingin Banda Aceh Menggunakan Modifikasi Biofilter Kaldness K1 dan Coral Sand - Raimon Raimon; Elvitriana Elvitriana; Muhammad Nizar (Jurnal Serambi Engineering, 2023)
This study aims to treat wastewater from the Al Mahira Lamdingin Market, Banda Aceh City using modified Kaldness K1 Biofilter and Coral Sand. Wastewater were filtered and precipitated in a vessel for 3 hours and then flowed into the Kaldness K1 Biofilter vessel and Coral Sand for 2 days. The treated water was then analyzed to obtain the characteristics of the main parameters such as pH, TSS, BOD, and COD. The results showed that wastewater from the Al Mahira Lamdingin Market had characteristics including pH 7.77 mg/l, BOD 224.9 mg/L, COD 627.92 mg/L, and TSS 336 mg/L, respectively. When wastewater treatment process was carried out using the Kaldness K1 Biofilter and Coral Sand with a contact time of 2 days, the concentration of each main parameter decreased to 98.3% (TSS), 98.7% (BOD), and 75.4% (COD). These results indicated that wastewater treatment process using the Kaldness K1 Biofilter and Coral Sand was effective for domestic wastewater treatment at Al Mahira Lamdingin Market, Banda Aceh City.